NILAI-NILAI AGAMA DAN PANDANGAN GENDER DI KALANGAN REMAJA MUSLIM - Safinah, Safinah (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2022)
This study aims to examine religious values and gender views among Muslim adolescents in three Madrasah Aliyah (MA) in Jambi. Using a qualitative approach through in-depth interviews, observations, and documentation, this study reveals how the understanding and application of religious values, as well as gender views, are shaped by the interaction between religious education in schools and family influence. The results show that although the understanding of religious values is generally strong, there are variations in their application that are influenced by academic and social pressures. Gender views among teenagers also show diversity, with some students holding conservative views while others are more progressive. These findings underscore the importance of an inclusive and dialogical approach to education to support the integration of religious values and gender equality. The implication of this research is the need for cooperation between schools, families, and communities to build a young generation that is insightful and committed to the values of justice and equality